Correlation between 6-min Walk Test and Cardiopulmonary Exercise Test in Chinese Patients - Pik-Fung Wong; Eric Yat-Tung Chan; Daniel Kwok-Keung Ng; Ka-Li Kwok; Ada Yuen-Fong Yip; Shuk-Yu Leung (Pediatric Respirology and Critical Care Medicine)
Aim: The aim of the study was to evaluate the correlation between the 6-min walk test (6MWT) and the cardiopulmonary exercise test (CPET) in Chinese pediatric patients. Methods: A retrospective review was undertaken for Chinese patients with exercise intolerance who had undergone both 6MWT and CPET on the same day over 21 months. Pearson's correlation analysis was used to examine the correlation between the 6-min walk distance (6MWD) and the maximum oxygen uptake (VO2max). The 6MWD was defined as abnormal if <10th percentile of height-matched reference, and the VO2maxwas defined as abnormal if <80% predicted. Results: Twenty-nine patients with a mean age of 14.3 ± 3.6 years were included in the study. The correlation coefficient (r) between the 6MWD and the VO2maxwas 0.457 with P = 0.013. Twenty-six (three excluded as no reference for VO2maxwas available for age <10 years) patients were analyzed. Using CPET as the gold standard for functional exercise capacity, 6MWT had a positive predictive value (PPV) of 92%, negative predictive value of 29%, sensitivity of 52%, specificity of 80%, and accuracy of 58% for assessing exercise capacity. Conclusion: 6MWT had a high PPV for abnormal CPET. It could still be used as a simple tool to evaluate patients with exercise intolerance.